Influence of drum motion parameters on shearer cutting properties - Chenxu LUO; Changlong DU; Songyong LIU (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
In order to study the influence of motionparameters of shearer drum on shearer cutting properties,an embedded system for cutting load test that can identify thecutting resistance indirectly were developed and put into test experimentunderground. The analysis results indicated that in the case of pullingspeed being constant, when pulling speed is small, the cuttingresistance nonlinearly declined and cutting specific energy consumption (CSEC)increases nonlinearly with the increase of the drum rotating speed; whenpulling speed is large, cutting resistance approximately linearly decreases andCSEC linearly increases with the increase of the drum rotating speed; in thecase of drum rotating speed being constant, the cutting resistance presentslinearly reducing form with pulling speed increasing its value in the range ofhigher speed and increases nonlinearly with pulling speed increasing its valuein the range of lower speed, and CSEC decreases nonlinearly with the increaseof the pulling speed. The consistency of the theoretical analysis and the testresults confirmed the reliability of the proposed embedded system whichprovides an effective way for the detection and analysis of mine shaft cuttingload and also provides the instruction for shearer speed-changing cutting coal. DOI : http://dx.doi.org/10.11591/telkomnika.v12i1.3191